Systems engineering : principles and practice - Kossiakoff, Alexander, 1914-2005; Seymour, Samuel J.; Flanigan, David A.; Biemer, Steven M. (Wiley series in systems engineering and management, 2020)
"Systems Engineering Principles and Practice continues to be a national standard textbook for the study of traditional systems engineering for advanced undergraduate and graduate students. It addresses the need for an introductory overview, first-text for the development and acquisition of complex technical systems. The material is organized in a way that teaches the reader how to think like a systems engineer and carry out best practices in the field. Since systems engineering is still developing as a discipline, there have been new concepts and practices that have entered the field since the text was originally published in 2003, and the second edition in 2011. An increasing number of students with diverse backgrounds and professions have used the text, leading to the need for new topics, expansion, integration and clarification. The proposed third edition is developed by two authors of the second edition and a new author, to upgrade this unique interdisciplinary guide to communicate the principles of good practice and alternative approaches to accomplish systems engineering goals"--